2021
DOI: 10.1017/s0022109021000211
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Mutual Funds Hold Lottery Stocks?

Abstract: We provide evidence regarding mutual funds' motivation to hold lottery stocks. Funds with higher managerial ownership invest less in lottery stocks, suggesting that managers themselves do not prefer such stocks. The evidence instead supports that managers cater to fund investors' preference for such stocks. In particular, funds with more lottery holdings attract larger flows after portfolio disclosure compared to their peers, and poorly performing funds tend to engage in risk shifting by increasing their lotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 121 publications
4
20
0
Order By: Relevance
“…Although these theories are proposed for the stock market, results in Table 2 suggest that they likely hold in the commodity futures market as well. This finding implies that institutional investors may also have behavioral biases, consistent with evidence in other markets (Agarwal et al, 2022; Boyer & Vorkink, 2014; Brown et al, 2018).…”
Section: Effect Of Idiosyncratic Asymmetry At the Characteristics Levelsupporting
confidence: 84%
See 1 more Smart Citation
“…Although these theories are proposed for the stock market, results in Table 2 suggest that they likely hold in the commodity futures market as well. This finding implies that institutional investors may also have behavioral biases, consistent with evidence in other markets (Agarwal et al, 2022; Boyer & Vorkink, 2014; Brown et al, 2018).…”
Section: Effect Of Idiosyncratic Asymmetry At the Characteristics Levelsupporting
confidence: 84%
“…Brown et al (2018) show that some hedge fund managers are sensation seeking and prefer lottery‐like stocks. Agarwal et al (2022) show that mutual fund managers with small size, younger, and relatively poor past performance are more likely to prefer lottery‐like stocks to attract more fund flows. Zhan et al (2022) find that stock characteristics that are well known to predict stock returns can also predict the cross section of delta‐hedged equity option returns, suggesting that even options traders may be subject to behavioral biases.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we control for two additional factors: fund lottery holding and the interaction terms between the fund return and market state dummies. As documented by Agarwal et al (2022), fund managers hold lottery-like stocks to cater to investors' lottery preferences. To untangle the effects of extreme returns and lottery holdings on future flows, we use funds' lottery holdings in the same period as an additional control.…”
Section: Variablementioning
confidence: 99%
“…Although lottery preference is generally more pronounced among individual investors (e.g., Kumar 2009) and the underperformance of lottery-like assets should be of less concern for mutual funds run by professional managers with diversified portfolios, recent studies have found that fund investors also exhibit preferences for funds with lottery-like payoffs. For example, Akbas and Genc (2020) find a positive and significant relationship between funds' maximum style-adjusted monthly returns and future flows, and Agarwal et al (2022) find evidence that some funds hold lottery-like stocks to cater for investors' lottery preferences, and these funds tend to underperform in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation